Nikolai Notovich is an Enthusiast of Russian Railways Concessions in Persia - Zaven A. Arabadzhyan (RUDN Journal of Russian History)
The author examines the struggle between the United Kingdom and Russia for the possession of railway concessions in Persia. On the Russian side, one of the participants was Nikolai Notovich. He opposed Russia's concessions to Britain and advocated for the intensification of Russian policy in this area. Over time, his views on the most profitable routes for the construction of railway tracks for Russia changed in accordance with the international situation, the balance of power between the main actors, and the 1907 Russian-British agreements on the division of Persia into spheres of influence. The latter led N. A. Notovich to the idea that under the new conditions it is no longer sensible to build a through road across Persia to the coast of the Persian Gulf or the Indian Ocean. Instead, he advised to focus on developing the railway network in the northern regions of the country, which would contribute to the growth of economic, political and cultural influence of Russia.